Improving Village Government Performance through Village Financial Management, Good Village Governance, and Knowledge Management - Wibisono, Nurharibnu; Asnawi, Nur; Ekowati, Vivin Maharani (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/Main Objectives: The purpose of this study is to investigate the influence of Village Financial Management (PKD), Good Village Governance (GVG), and Knowledge Management (KM) on Village Government Performance (KPD) from a sharia economic perspective. Background Problems: Due to the substantial influx of village funds following the introduction of Law No. 6/2014, the Village Government and Village Financial Management Officers (PPKD) must effectively and precisely handle village finances. Novelty: This study proves that good PKD, GVG, and KM development as an adaptation to changes in regulations, technology, corruption prevention, and calls for administrative change can enhance the Village Government's effectiveness. Research Methods: The study takes a quantitative method with simple random sampling procedure. The study's population was all villages in Madiun Regency, totaling 198 villages. Proportionally selected 66 villages from 15 sub-districts and 348 respondents of Village Financial Management Implementers (PPKD). Multiple regression using the SmartPLS 4 test tool was the data analysis method. Finding/Results: Multiple regression using the SmartPLS 4 test tool was the data analysis method. Conclusion: To implement bureaucratic reform and New Public Management, the Village Government must continue to improve PKD and GVG and foster KM as a way to serve the public, be accountable to the public, and work toward the village's vision and goal.